Study on Improvement of Recovery Characteristics of GdBCO Non-inductive coil for resistive SFCL. (June 2020) - Yanai, S.; Maeda, C.; Shirai, Y.; Shiotsu, M.; Isojima, S.
Abstract: Using the practical application of the resistance SFCLs (Superconducting Fault Current Limiter), it is required to quickly return to the superconducting state after interruption of the fault current. The quick recovery needs to improve the cooling property of a superconducting tape. It is confirmed that the recovery characteristics of a superconducting tape can be improved by the PTFE (PolyeTetraFluoroEthylene) coating or applying pressure. In this paper, we used GdBCO tapes for the resistive SFCL and investigated the effect of the PTFE coating or applying pressure for improvement of its recovery characteristics of non-inductive coil. Besides, we observed the boiling phenomena on the surface of the part of GdBCO tapes between under pressurized conditions and ambient pressure by a high-speed video camera.